Damage and residual layer analysis of reactive ion etching textured multi-crystalline silicon wafer for application to solar cells. (February 2022) - Kang, Dongkyun; Park, HyunJung; Choi, Dongjin; Han, Hyebin; Seol, Jaeseung; Kang, Yoonmook; Lee, Hae-Seok; Kim, Donghwan
Highlights: Removal of byproducts and plasma damage layers caused by reactive ion etching. Calculation of short circuit current density considering weighted average reflectance. Maintains low reflectance after damage removal etching and increases efficiency of multi-crystalline silicon solar cells. Abstract: As part of the surface texturing process of multi-crystalline silicon solar cells, isotropic etching is performed by using an acidic solution. Furthermore, metal catalyst chemical etching (MCCE), reactive ion etching (RIE), and laser etching are used to further decrease surface reflectance. This study aimed to increase the power conversion efficiency of the solar cell by improving the short-circuit current density (Jsc ) using MCCE and RIE. During RIE, a byproduct and a plasma damage layer are formed on the silicon surface, which decrease the efficiency of the solar cell and therefore need to be identified and effectively removed. Transmission electron spectroscopy, energy dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy analyses were performed to identify the byproducts formed during RIE to confirm that it was amorphous silicon oxide. Furthermore, an etching process using acidic and alkaline base solutions was used to remove the plasma damage layer and the Jsc loss was calculated using the reflectance. As a results, confirm a difference of up to ∼ 1.6 mA/cm 2, and an improvement of approximately 0.6% was observed in the solar cell efficiency. These results show a method of minimizing Jsc loss and removing surface damage in a silicon solar cells fabricated using the RIE method.